2011
DOI: 10.1093/jac/dkr150
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase I function during Escherichia coli response to antibiotics and stress enhances cell killing from stabilization of its cleavage complex

Abstract: Bacterial topoisomerase I function is actively involved in the SOS response to antibiotics and stress challenge. Cell killing initiated by the topoisomerase I cleavage complex would be enhanced by antibiotics and the host response. These findings provide further support for bacterial topoisomerase I as a therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Furthermore, the recA mutation resulted in a pDNA supercoiled fraction of 68 ± 8% (Figure 1C). It has been shown that RecA protein participates in the regulation on toposiomerase A gene ( topA ) [31]. Therefore, it is possible that recA mutants display a higher topoisomerase activity, which helps to explain the effect observed in VH33 Δ recA .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the recA mutation resulted in a pDNA supercoiled fraction of 68 ± 8% (Figure 1C). It has been shown that RecA protein participates in the regulation on toposiomerase A gene ( topA ) [31]. Therefore, it is possible that recA mutants display a higher topoisomerase activity, which helps to explain the effect observed in VH33 Δ recA .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been identified in Salmonella spp. recovered from chickens in Japan, and in E. coli of poultry origin in Spain or of pig origin in China (Liu et al, 2011; Soufi et al, 2011; Du et al, 2012). Since this gene seems to be geographically widespread, stable over the time, and equally prevalent in ciprofloxacin-susceptible and -resistant strains (Park et al, 2006), its significance remains debatable.…”
Section: Plasmid-mediated Resistancementioning
confidence: 99%
“…More recently, a role of topoisomerase I was observed in E. coli SOS response (Liu et al, 2011; Yang et al, 2015), which prompted us to verify the possibility of a direct physical interaction between these proteins. Purified His-EcTOP1 and RecA were incubated together in the presence of ATP, and pulled-down with Cobalt agarose resin.…”
Section: Resultsmentioning
confidence: 99%